Produksi karkas, nilai gizi dan profil asam lemak daging serta produksi limbah kelinci New Zealand White akibat penyertaan rumput laut cokelat (Sargassum sp.) pada ransum - Sutaryo Sutaryo; Alief Jannah; Auliya Rizqi; Dian Lestari; Agung Purnomoadi (Livestock and Animal Research, 2021)
Objective: The aim of this current paper was to evaluate effect of inclusion Sargassum sp. in the ration on meat nutrient content, meat fatty acid profile and waste production of New Zealand White (NZW) rabbit.Methods: Twenty four NZW rabbit (70-80 d old) with initial body weight 1736 ± 50 g were randomly allocated in to three treatments. The treatments were: T1 basal feed, T2 inclusion of 4% Sargassum sp. in the basal feed and T3 inclusion of 8% Sargassum sp. in the basal feed.Results: Results of this experiment showed that inclusion of Sargassum sp. in the ration gave no effect (P>0.05) on the moisture, ash, crude protein content of Longisimus dorsi (LD) muscle, carcass percentage, warm carcass weight, cold carcass weight and waste production. However, the treatment was significantly (P<0.05) decreasing fat content of LD muscle. Fatty acids profile of all treatments was relatively same.Conclusions: Utilization of Sargassum sp. in the rabbit ration up to 8% has no impact on the carcass production, protein, ash, and meat water content, and the waste production. Even the inclusion of Sargassum sp. the ration at level of 4% can reduce the fat content of rabbit meat. Thus, based on the observed parameters Sargassum sp. can be used to substitute rabbit feed up to a level of 8%.